Kulinaryzmy i kulinaria w języku biznesowym w glottodydaktyce italianistycznej na podstawie podręczników „L’italiano in azienda” (2002) i „Un vero affare!” (2015) - Godzich, Anna; Machowski, Szymon (Neofilolog, 2024)
The article is devoted to analyzing the cultural context typical for food and its associated etiquetteand rituals from 2 coursebooks on the Italian Business language, and aims at a) investigating to what extent coursebooks in Business Italian include both theoretical and practical content information on the Italian dining culture; b) reconstructing guidelines on etiquette for dining and socializing in professional settings in companies and with regard to the role of language in culture (Hall, 1976, Bańczerowski, et al., 1982). These objectives were fulfilled by performing a semantic analysis of the lexical content of 2 coursebooks by Giovanna Pelizza and Marco Mezzadri (2002 and 2015). For this purpose, a lexical corpus was formed by extracting single-word culinary-related lexical items from the coursebooks. The remaining sources related to food in business culture (Meyer, 2023) was used as a point of reference for validation of the small corpus.